Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-16T23:00:08+01:00
( 4(2x + 3) - 2(4y - 1) = 30
( [5x + 1/3] - [y - 3/4] = 3 /*12

( 8x + 12 - 8y + 2 = 30
( 4(5x + 1) - 3(y - 3) = 3*12

( 8x - 8y = 30 - 12 - 2
( 20x + 4 - 3y + 9 = 36

( 8x - 8y = 16 /:8
20x - 3y = 36 - 4 - 9

( x - y = 2
( 20x - 3y = 23

( x = 2 - y
( 20(2 - y) - 3y = 23

( x = 2 - y
( 40 - 20y - 3y = 23

( x = 2 - y
( -20y - 3y = 23 - 40

( x = 2 - y
( -23y = -17 /:(-23)

( x = 2 - y
( y = ¹⁷/₂₃

( x = 2 - ¹⁷/₂₃
( y = ¹⁷/₂₃

( x = 1⁶/₂₃
( y = ¹⁷/₂₃